Transdisciplinary engaged learning: Upskilling with communication strategies in bioinformatics - Griffith, Mary (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
This study highlights an innovative educational project entitled ‘Dynamic Teaching through Communication Skills’ as well as forming part of joint initiative for Erasmus + Communities and Students Together (CaST) 2019-1-UK01-KA203-061463. The pilot study shows that there are many ways to approach teaching across the disciplines with Engaged Learning. The proposal includes discussions on the practical methodologyof integrated content and language in higher education. While bringing real worldproblem solving into the Health Engineering degree, the chapter underscores aspects of persuasion and pitch development within the paradigm of English as a LinguaFranca.